Generalized Pustular Psoriasis pada Pasien Diabetes Melitus Tipe 2: (Case Report) - Asmaul Khusna; Heffi Anindya Putri (Pusat riset dan Inovasi Nasional, 2026)
Generalized pustular psoriasis (GPP) is a severe inflammatory form of psoriasis characterized by widespread sterile pustular eruptions. Pro-inflammatory mediators released during chronic inflammation may contribute to comorbidities, including type 2 diabetes mellitus (T2DM). A 65-year-old woman presented with pustular eruptions over almost the entire body for seven days, accompanied by burning sensation and pruritus. Some pustules coalesced forming “lakes of pus,” while others appeared as erythematous plaques with coarse white scales. The patient had a history of T2DM. Based on clinical findings, the patient was diagnosed with GPP. She was hospitalized for seven days and followed up weekly until week 10. Inflammatory mediators such as Th-1, TNF-α, IL-6, IL-7, IL-8, IL-17, and IL-23 in psoriasis may inhibit insulin receptor signaling and glucose uptake, leading to insulin resistance and increased blood glucose levels. The duration of treatment until remission in psoriasis patients with T2DM tends to be longer than in non-diabetic patients. In patients with comorbidities, low-dose methotrexate (5–7.5 mg/week) was administered. The coexistence of GPP and T2DM may lead to more severe exacerbations, prolonged treatment duration, and reduced quality of life, posing challenges in management.